Do 'Sin Stocks' deprive Islamic stock portfolios of diversification? Some insights from the Use of MGARCH-DCC - Mustaffa Kamil, Nazrol Kamil; Bacha, Obiyathulla Ismath; Masih, Mansur (Malaysian Finance Association, 2012)
There is this argument that Shari’ah compliant portfolios are at a disadvantage in terms of portfolio diversification given that the exclusion of ‘sin stocks’ shrinks the Islamic investor’s investment universe. This paper investigates first, whether there is empirical evidence to substantiate such a claim, and second, can something be done to alleviate this disadvantage. Our results show that there is statistical evidence that Islamic portfolios are deprived of some benefits of diversification, at the sector level. However, the empirical evidence does not permit us to generalise such a finding at the specific stock level. By analysing the temporal characteristics of correlations using MGARCH-DCC, we argue that Islamic portfolios can minimise loss of diversification benefit by adopting appropriate portfolio allocation strategies. In particular, market sentiment and commodity prices are two key variables that can drive portfolio allocation switching decisions. In short, while there is some evidence that investors of Shari’ah compliant portfolios are denied additional benefits of diversification, there are arguably avenues to mitigate such a disadvantage.